Different responses of abundant and rare bacterial composition to groundwater depth and reduced nitrogen application in summer maize field - Bai, Fangfang; Guo, Wei; Li, Ping; Qiao, Dongmei; Du, Zhenjie; Qi, Xuebin (Frontiers in Microbiology, 2023)
It is well known that reduced nitrogen application and groundwater depth can change soil microbial communities, but the associated difference in the response of abundant and rare bacterial composition to these local environmental changes remains unclear. In this study a lysimeter experiment was carried out to examine the impact of reduced nitrogen and groundwater depth on the composition of abundant and rare bacteria. Our results demonstrated that the summer maize field soil species composition of rare bacterial sub-communities was significantly regulated by reduced nitrogen application, groundwater depth change and their interactions. However, only reduced nitrogen application had a significant influence on the species composition of abundant bacterial sub-communities. The structural equation model (SEM) indicated that reduced nitrogen application and groundwater depth change also could indirectly regulate the species composition of abundant and rare bacteria by altering soil attributes. The changes in soil pH and TSN had the most significant effects on the community composition of abundant and rare bacteria, respectively. More importantly, rare bacterial subcommunities were more sensitive to the changes in nitrogen input, groundwater depth and soil factors. Collectively, our study first demonstrated that abundant and rare microbial sub-communities responded differently to reduced nitrogen application and groundwater depth change. This study highlights that summer maize farmland production management should take nitrogen input and groundwater depth into consideration to maintain the compositional stability of soil rare microbial sub-communities.